Validity, intra and inter‐reliability of manual evaluation of the respiratory muscle strength in asthmatic patients. (9th June 2020) - da Luz Goulart, Cassia; Trimer, Renata; Garcia‐Araujo, Adriana Sanches; Caruso, Flavia Rossi; Ricci, Paula Angélica; dos Santos, Polliana Batista; Mendes, Renata Gonçalves; Borghi‐Silva, Audrey
Abstract: Objective: This study investigated the concurrent validity, inter and intra‐reliability of manual evaluation in Asthma patients. Methods: Twenty six asthma patients were assessed. Maximal respiratory muscle strength (Mrms) was tested by inspiratory and expiratory pressure (MIP and MEP, respectively) trough manovacuometer. In addition, Mrms of diaphragm (anterior and posterior), Intercostals (lower and upper portion) and Rectus abdominal were obtained manually, according to Medical Research Council (MRC) scale. Two independents evaluators, previously trained, made both measurements. Results: Reproducibility of Mrms intra‐evaluators: anterior diaphragm (ICCs, 0.79 and 0.67); Posterior portion of the diaphragm (ICCs, 0.43 and 0.51); Upper intercostals (ICCs, 0.47 and 0.40); Lower intercostals (ICCs, 0.81 and 0.51) and rectus abdominal (ICCs, 1.0). Inter‐reproducibility of anterior diaphragm was low to moderate, while intercostals (upper and lower portion) was relatively low. However, rectus abdominal presented high reproducibility reflecting in almost perfect agreement. In addition, we found positive correlations between MIP versus Lower Intercostals ( r = .60, p = .007) and MEP versus rectus abdominal ( r = .41, p = .04). Conclusion: In asthmatic patients, manual evaluation of the respiratory muscles is reliable. In addition, maximal respiratory pressures using manometer assessment were related to manual evaluation, in special to diaphragm and rectus abdominal muscles.